Enhancing Vocational High School Students’ Technological Competence through Python and Artificial Intelligence - Mikha Dayan Sinaga; Zhafran Fatih Ananda; Akbar Idaman; Muhammad Irfan; Oswald Tobias Rafaello Siahaan (Penerbit Goodwood, 2026)
Purpose: This study aims to enhance the technological competence of vocational high school students through the introduction of Python programming and Artificial Intelligence (AI) to improve their digital literacy and computational thinking skills. Methodology: This study was conducted at Sekolah Menengah Kejuruan (SMK) Sultan Iskandar Muda, involving 44 tenth-grade vocational high school students. The program applied a quasi-experimental approach with a pretest–posttest design to measure students’ understanding before and after training. The training activities included lectures, demonstrations, and hands-on coding practice using Python 3.10, Google Colab, and Microsoft PowerPoint as learning tools. Data were collected through questionnaires, observations, and evaluation tests to measure the students’ knowledge of programming concepts and AI applications. Results: The results showed a significant improvement in students’ understanding after they participated in the training program. The average pretest score of 53.5 increased to 82.8 in the post-test. Students demonstrated better comprehension of Python programming concepts, including syntax, variables, data types, and input–output commands, as well as greater awareness of Artificial Intelligence applications in everyday life. Conclusions: The training program effectively improved students’ technological competence and increased their interest in learning programming and in emerging technologies. Limitations: The study was limited by the short training duration and differences in students’ initial knowledge levels. Contributions: This study contributes to vocational and technology education by providing a practical training model that can support the development of students’ digital literacy and readiness to face the challenges of the digital transformation era.